Low‐T CO Oxidation over Cu−CHA Catalysts in Presence of NH3: Probing the Mobility of CuII Ions and the Role of Multinuclear CuII Species. Issue 15 (4th June 2020) - Villamaina, Roberta; Iacobone, Umberto; Nova, Isabella; Ruggeri, Maria Pia; Collier, Jillian; Thompsett, David; Tronconi, Enrico
Abstract: We use dry CO oxidation to probe Cu II dimers in Cu−CHA catalysts in the presence of ammonia. Samples with different Cu/Al and Si/Al ratios were exposed to CO in He at 200 °C after either one of two catalyst pre‐treatments: (i) pre‐oxidization in 8 % O2 /He at 550 °C for 1 hour; (ii) pre‐oxidation in 8 % O2 /He at 550 °C for 1 hour followed by NH3 saturation at 200 °C in O2 . Pre‐adsorbed NH3 was necessary to observe a significant CO2 evolution, the rate of CO2 formation being second order in the Cu II OH fraction of the Cu II sites. This is direct evidence that NH3, not involved in the CO oxidation chemistry, favours the formation of Cu II dimers with removable oxygen by ligating with and mobilizing isolated Cu II OH ions, otherwise inactive. These findings are relevant for the low‐temperature NH3 −SCR redox mechanism over Cu−CHA, in which Cu II dimers may play a role in parallel or in alternative to the isolated Cu II sites so far proposed for the reduction half cycle of standard SCR. Abstract : CO oxidation : In CO titration experiments over pre‐oxidized Cu−CHA catalysts, the CO2 formation was enhanced by NH3 . This is evidence that NH3 ligands mobilize isolated Cu II ions to form the dimeric complexes with removable oxygen necessary for CO oxidation, as confirmed by transient kinetic analysis: the rate of Cu II reduction was 2 nd order in the ZCu II OH species. The relevance for the reduction half cycle in the redox mechanism of standard SCR is discussed.